Temperature Cycle-Induced Deracemization of Cl-TAK Using Amberlyst A26: A Heterogeneous Catalyst Approach for Efficient and Reusable Racemization - Jin Maeda; Pascal Cardinael; Gerard Coquerel; Adrian Flood (Chemistry Proceedings, 2024)
This study investigates the feasibility of employing Amberlyst A26 as a racemizing agent for the temperature cycle-induced deracemization (TCID) of the model compound Cl-TAK (1-(4-chlorophenyl)-4,4-dimethyl-2-(1H-1,2,4-triazol-1-yl) pentan-3-one). We assessed Amberlyst A26 for its potential as a reusable heterogeneous catalyst, compatible with various solvents and easily separable from the solution. Racemization rates at 20 °C and 25 °C confirmed its suitability, with experiments showing that Cl-TAK undergoes racemization only in the presence of the catalyst. TCID experiments with Amberlyst A26 yielded successful deracemization, achieving an 88% enantiomeric excess from an initial 30%. These findings highlight Amberlyst A26’s viability for industrial-scale TCID applications, emphasizing reusability and cost efficiency.